Theological themes of the Millennial Kingdom in the writings of Ellen White - Bohdan Kuryliak (Мультиверсум: Философский альманах)
The Millennial Kingdom (Rev. 20) has been a controversial topic in Christian theology, including in the 19th century, when the Seventh-day Adventist Church emerged. One of the founders of the Adventist Church was Ellen White, whose writings play an important role in both the practical life and theology of Adventists. Among the many studies of theological concepts in the writings of Ellen White, the topic of the Millennial Kingdom remains unexplored. This article is the first attempt to identify the theological themes of the millennium in the writings of Ellen White. Analysis shows that White accepted a literal interpretation of the millennium and took a premillennial approach. White adhered to a linear sequential chronology and considered the thousand years and the resurrection to be real events. Her unyielding devotion to premillennial views led her to reject alternative interpretations of this passage, even classifying some as false and potentially harmful to salvation. Ellen White showed three major theological themes in her interpretation of Revelation 20. The first major theological theme concerns the ultimate destiny of mankind. White argued that at the end of the age, there would be a double resurrection of the dead: first for the righteous and second for the wicked. These resurrections differ in the composition of participants, timing, and the nature of the resurrected persons. The second major theological theme is the final judgment, in which God will judge both sinners and the forces of evil, including demons and Satan. For a thousand years, the resurrected righteous will take part in this judgment. The actions of sinners will be evaluated, and their punishment will be determined based on their deeds. Ellen White’s third theological theme of Revelation 20 is the practical life of the Christian. White focused on the need for personal repentance, responsibility, and dedication to God.